Coaching Practices and Learning Capability: Drivers of Lecturer Performance Management - Dewiana Novitasari (Yayasan Aya Sophia Indonesia, 2024)
This study examines the potential relationship between performance and more coaching practice attention, taking learning capability into account as a mediating factor. 61 instructors at a private institution in Jakarta provided data for the study utilizing quantitative techniques and follow-up questionnaires. This study demonstrates that coaching, either directly or indirectly through the mediation of learning potential, has a favorable and significant impact on lecturer performance. The findings of this study may have a big impact on how HR managers make decisions on how to train university instructors and introduce new tools. This research also aids university HR management in guiding their strategic planning for campus HR and critically evaluating HR development investment plans in the form of coaching methods.